Radiological Assessment of Distraction Osteogenesis of Large Bone Defect in Lower Extremity Long Bone: A Descriptive Study - Barnawal, Satish Prasad; Gandhi, Suresh; Rathod, Avinash (Nepal Orthopaedic Association Journal, 2023)
Introduction: Bone defect is difficult to manage. Objective of this study was to assess radiological parameters of distraction osteogenesis of large long bone defects.Methods: Descriptive study was carried out in department of orthopedics, Jawaharlal Institute of Postgraduate Medical Education and Research Pondicherry, India during April 2018-March 2019. Inclusion criteria were bone gap of more than 5cm either in tibia or femur, skeletal maturity, bone defect due to trauma or excision of tumor; and bone transport by either by Ilizarov or linear reconstruction system. Patients with incomplete data, poly-trauma, and brain injury were excluded. A senior orthopedic surgeon performed all surgeries. Well-trained orthopedic surgeons collected data. Outcome variables were bone union, primary bone length, length of bone gap, implants type, duration of apparatus, number of days of distraction, percentage of transport, distraction speed and bone healing index. Results: Mean age of participants was 33.8 years. All of them were males. Road traffic accident was cause for bone loss in 80 % of cases. Bone union was attained in all patients. Bone loss of up to 15 cm was gained by distraction osteogenesis. Range of bone gap was from 5.38 cm to 15 cm. 6.9 to 17.66 months were required for complete union and removal of fixator. Up to 46 % of bone transport was possible with Ilizarov. Two patients were treated with additional intramedullary nail. Conclusion: Distraction osteogenesis can achieve union in large bone defect up to 15 cm in tibia and femur. Additional internal fixation with an intramedullary nail can be beneficial.